POTENCY OF BLACK TEA FILTRATE AS UV PROTECTANT TO S/NPV JTM 97 C IN CONTROLLING HELICOVERPA ARMIGERA ON SOYBEAN - Anella Retna Kumala Sari; Tiara Eka Ariestantia; Fery Abdul Choliq (Jurnal Penelitian Tanaman Industri, 2020)
Helicoverpa armigera is the important pest on soybean which  usually controlled by chemical insecticide spraying, so it should be replaced by naturally control using biological agents such as Spodoptera litura Nuclear Polyhedrosis Virus (S/NPV) JTM 97 C. It has some weakness such as during it’s applied in the field the effectiveness can become decreased after exposure the sunlight, especially ultraviolet (UV) so it needs the protective material, such as black tea filtrate which is known containing epigallocatechin gallate, caffeic acid, and apigenin which have role as UV protectors. This research aimed to investigate the potential of black tea filtrate to protect the S/NPV JTM 97 C from UV in controlling of H. armigera. The research was conducted in Pests and Diseases Laboratory on Indonesian Legumes and Tuber Crops Research Institute (ILETRI), Kendalpayak, Malang from January to June 2015. The research used Completely Randomized Design with seven treatments and four replications. They were S/NPV JTM 97 C without UV protectant as control (P1), S/NPV JTM 97 C + kaolin as comparison (P2), S/NPV JTM 97 C + black tea  filtrate concentration 0.5 (P3), 1.0 (P4), 1.5 (P5), 2 (P6), and 2.5% (P7). Results showed that all of the protective materials of black tea filtrate were unable to provide mortality of H. armigera larvae better than kaolin. Kaolin can cause mortality of H. armigera larvae up to 82,50%. All of Black tea filtrate concentrations tested were not able  to be used as  protectant of  S/NPV JTM 97 C due to it can only cause mortality of H. armigera up to 47,50% .  Keywords: Entomopathogenic virus,  LC50, protectant material,  pest.